2018
DOI: 10.1111/echo.13833
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of postoperative atrial fibrillation with left atrial mechanical functions and NT‐pro ANP levels after coronary artery bypass surgery: A three‐dimensional echocardiography study

Abstract: It was found that 3D echocardiography can be used as a helping noninvasive method to show subclinical atrial volume and mechanical dysfunction in patients undergoing CABG. Also, blood levels of NT-pro ANP in POAF group were increased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 22 publications
2
9
0
1
Order By: Relevance
“…Studies have shown that MR-proANP levels were associated with increased left atrial size, presence of low-voltage areas (LVAs), and AF progression stage. 14,15 Similar findings in terms of left atrial size were also present within our investigation. Previously, a large observational study outlined the importance of MR-proANP in a broad AF population reflecting an increased risk for AF burden and adverse events with increasing plasma values.…”
Section: Pathophysiological Aspects Of Mr-proanpsupporting
confidence: 90%
“…Studies have shown that MR-proANP levels were associated with increased left atrial size, presence of low-voltage areas (LVAs), and AF progression stage. 14,15 Similar findings in terms of left atrial size were also present within our investigation. Previously, a large observational study outlined the importance of MR-proANP in a broad AF population reflecting an increased risk for AF burden and adverse events with increasing plasma values.…”
Section: Pathophysiological Aspects Of Mr-proanpsupporting
confidence: 90%
“…В нашем исследовании увеличенный диаметр ЛП ассоциировался с риском возникновения ПОФП, что подтверждается результатами литературы [9,10]. ПОФП имеет два основных патофизиологических механизма, которые могут быть связаны с размерами ЛП: дегенеративные изменения миокарда предсердий и предоперационные электрофизиологические изменения.…”
Section: Discussionunclassified
“…In a study by Anatolevna et al, left atrial dimensions as well as increased postoperative IL-6, IL-8, and superoxide dismutase were identified as predictors of PoAF (8), while advanced age, low preoperative creatinine clearance, and increased left atrial diameter were reported to be independent predictors of PoAF in the study by Ferreira et al (9). On the other hand Hidayet Ş. et al emphasised that LA volume index (LAVİ) and mechanical functions are better indicator than LA diameter in new onset PAF after CABG (10). Also, vitamin D deficiency was reported to be an independent predictor for PoAF in the study by Emren et al, and increased serum uric acid levels had a predictive role for PoAF in the study by Memetoglu et al (,11,12).…”
Section: Discussionmentioning
confidence: 99%